First Laws: Tikanga Māori in/and the Law - Ruru, Jacinta (Victoria University of Wellington Law Review, 2018)
This address is the 10th Shirley Smith Memorial Lecture given in Wellington on 18 October 2017. It considers the possibility for the enhanced role of first laws – the laws of Indigenous peoples – within contemporary settler legal systems.